Gender differences in eating habits and lifestyles of young students: observational evaluation from MaestraNatura program - Silenzi, Annalisa; Giona, Letizia; Zanchi, Giulia; Tammaro, Alessia; Monteleone, Valentina; D’Archivio, Massimo; Santangelo, Carmela; Masella, Roberta; Scazzocchio, Beatrice; Varì, Rosaria (Frontiers in Nutrition, 2025)
IntroductionUnhealthy diet and sedentary life represent the main risk factors for chronic NonCommunicable Diseases. Investing in children’s health education leads to benefits for their whole lifespan and the whole of society. MaestraNatura (MN) is an education program addressed to increase knowledge and skills about food and nutrition in students from primary and first-level secondary school. The main objective of the present paper was to evaluate eating habits and the adherence to the principles of the Italian dietary guidelines (IDG) of 8–14 years old children to identify possible influences of gender and parents on their eating choices and behaviors. Therefore, the potential benefits of MN on promoting changes in lifestyle and dietary patterns were also evaluated.MethodsQuestionnaires on eating habits and physical activity were completed by 1,037 students and 220 parents from primary and secondary schools from 6 Italian regions. One hundred fifty-eight questionnaires were filled in by a subgroup of secondary schools’ students before and after two consecutive years of MN program. Differences between groups in the responses to questions were assessed by Chi-squared (χ2) tests. Differences in the IDG adherence score were assessed by analysis of variance (ANOVA), with gender (males, M vs. females, F) and/or type of school as between-subjects’ factors, as appropriate.ResultsThe questionnaires showed an average degree of adherence to the principles of the IDG for children with a similar distribution in M and F. Analysis of individual responses revealed differences between F and M in daily consumption of vegetables (F > M), water (M > F), and in weekly consumption of nuts (F > M) and commercial cookies (M > F). Furthermore, M are more engaged in physical exercise compared to F. Results from a subgroup of students attending MN for two consecutive years showed increases in the consumption of water, vegetables, fruit and legumes, and a decrease in the intake of commercial snacks, as well as an increase in physical activity.ConclusionItalian children evidence gender differences in eating behaviors. Specific nutrition programs are needed to raise children’s awareness of the importance of a healthy lifestyle and to correct eating habits.